1.
а) (3y - 2)(3y + 2) = 9y² - 4
б) (3y - 1)² = 9y² - 6y + 1
в) (4a + 3k)(4a - 3k) = 16a² - 9k²
2.
(b-8)² - (64 - 6b) = b² - 16b + 64 - 64 + 6b = b² - 10b = b(b - 10)
3.
a) 25 - y² = (5 - y)(5 + y)
б) a² - 6ab + 9b² = a² - 2×1×3ab + (3b)² = (a - 3b)²
4.
36 - (6 - x)² = x(2,5 - x)
36 - (36 - 12x + x²) = 2,5x - x²
12x + x² = 2,5x - x²
2x² + 9,5x = 0
x(2x + 9,5) = 0
x = 0 или 2x = -9,5
x = 0 или x = -4,75
ответ: 0; -4,75
5.
а) (c² - 3a)(3a - c²) = -(3a - c²)(3a - c²) = -(3a-c²)²
б) (3x + x³)² = 9x² + 6x⁴ + x⁶
в) (3 - k)²(k+3)² = (3 - k)²(3+k)² = [(3-k)(3+k)]² = (9 - k²)²
6.
а) (3x - 2)² - (3x - 4)(4 + 3x) = 0
(3x - 2)² + (4 + 3x)² = 0
9x² - 12x + 4 + 16 + 24x + 9x² = 0
12x + 20 = 0
12x = -20
3x = -5
x = -5/3
б) 25y² - 64 = 0
y² = 64/25
y = ± 8/5
7.
а) 36a⁴ - 25a²b² = a²(36a² - 25b²) = a²(6a - 5b)(6a + 5b)
б) (x - 7)² - 81 = (x - 7 - 9)(x - 7 + 9) = (x - 16)(x + 2)
Объяснение:= b2 - 4ac = 92 - 4·2·10 = 81 - 80 = 1
x1 = -9 - √1 2·2 = -9 - 1 4 = -10 4 = -2.5
x2 = -9 + √1 2·2 = -9 + 1 4 = -8 4 = -2
D = b2 - 4ac = 172 - 4·1·0 = 289 - 0 = 289
x1 = -17 - √289 2·1 = -17 - 17 2 = -34 2 = -17
x2 = -17 + √289 2·1 = -17 + 17 2 = 0 2 = 0
D = b2 - 4ac = 82 - 4·5·(-4) = 64 + 80 = 144
x1 = -8 - √144 2·5 = -8 - 12 10 = -20 10 = -2
x2 = -8 + √144 2·5 = -8 + 12 10 = 4 10 = 0.4
D = b2 - 4ac = (-2)2 - 4·7·(-14) = 4 + 392 = 396
x1 = 2 - √396 2·7 = 1 7 - 3 7 √11 ≈ -1.2785534815808857
x2 = 2 + √396 2·7 = 1 7 + 3 7 √11 ≈ 1.5642677672951713
= b2 - 4ac = (-7)2 - 4·1·12 = 49 - 48 = 1
x1 = 7 - √1 2·1 = 7 - 1 2 = 6 2 = 3
x2 = 7 + √1 2·1 = 7 + 1 2 = 8 2 = 4
ответ: пk/2; пn/5; п/2+пm, где k, n, m - целые числа